2017
DOI: 10.1021/acs.chemmater.7b03863
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/Chitosan Compact Polyelectrolyte Complexes: A Cell and Bacterial Repellent Material

Abstract: Ultracentrifugated compact polyelectrolyte complexes (uCoPECs) represent a new class of materials that are obtained by ultracentrifugation of solutions of polyanion/polycation complexes in the presence of salt. In the present study, two polysaccharides, chitosan and alginate, were used to form such complexes, thus providing a solid material uniquely composed of polysaccharides. The conditions for obtaining the uCoPEC material were optimized: the optimal salt concentration and polysaccharide concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…Our findings are consistent with experiments conducted on ultracentrifugated compact polyelectrolyte complexes formed from chitosan and alginate, which also demonstrated negligible killing of Staphylococcus aureus . 58 Charge-neutral polyelectrolyte complexes do not exhibit the antibacterial properties of their cationic polyelectrolyte components. Liquid complex coacervates have also been reported to be biocompatible with mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with experiments conducted on ultracentrifugated compact polyelectrolyte complexes formed from chitosan and alginate, which also demonstrated negligible killing of Staphylococcus aureus . 58 Charge-neutral polyelectrolyte complexes do not exhibit the antibacterial properties of their cationic polyelectrolyte components. Liquid complex coacervates have also been reported to be biocompatible with mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 Another study described how ultracentrifugated compact PECs from chitosan and alginate resisted the adhesion of Staphylococcus aureus. 58 While this result is encouraging, there is a benefit to developing alternative processing strategies that are less energy intensive and can be performed at scale to enable the use of PECs as antifouling coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a seminal report by Wang and Schlenoff demonstrated that solid precipitates and liquid coacervates could exist along a continuum of salt concentration ( Figure 10). 50 This idea of salt-driven plasticization, or 'salo- plasticity' has opened up a tremendous range of opportunities for using salt to process polyelectrolyte complex materials as liquid coacervates, and then solidify the materials by the removal of salt, and a range of accounts describing ultracentrifuged [190][191][192][193] or extruded materials, 194 spin-coated films, 195,196 3D printed structures, 197 and electrospun fibers 65,198,199 have been reported.…”
Section: Coacervate Rheology and The Complex/coacervate Continuummentioning
confidence: 99%
“…This is a procedure analogous to that reported for the compaction of PECs constituted of alginate and chitosan which allows for the preparation of highly hydrated hydrogels in the presence of salt. 24,25 After centrifugation (compaction stage), and removing the supernatant, the precipitates from all the samples presented a hydrogel-like aspect as can be observed in Fig. 3.…”
Section: Paper Materials Advancesmentioning
confidence: 78%